2019
DOI: 10.1302/0301-620x.101b6.bjj-2018-1348.r1
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty has a higher risk of revision due to infection than anatomical shoulder arthroplasty

Abstract: Aims The aim of this study was to use national registry database information to estimate cumulative rates and relative risk of revision due to infection after reverse shoulder arthroplasty. Patients and Methods We included 17 730 primary shoulder arthroplasties recorded between 2004 and 2013 in The Nordic Arthroplasty Register Association (NARA) data set. With the Kaplan–Meier method, we illustrated the ten-year cumulative rates of revision due to infection and with the Cox regression model, we reported the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 20 publications
1
20
0
3
Order By: Relevance
“…11,20 Some authors have also found a higher rate of deep infection in patients undergoing RSA when compared with TSA. 16,21 In addition, restoration of motion seems to be superior with anatomic TSA, especially in terms of internal rotation.…”
mentioning
confidence: 99%
“…11,20 Some authors have also found a higher rate of deep infection in patients undergoing RSA when compared with TSA. 16,21 In addition, restoration of motion seems to be superior with anatomic TSA, especially in terms of internal rotation.…”
mentioning
confidence: 99%
“…Moeini et al 11 report about a 10-year cumulative revision rate for reverse arthroplasties of 8% as a result of the analysis of n = 17730 arthroplasties in the Nordic Arthroplasty Register Association from Denmark, Norway, and Sweden. Based on the same registry, Lehtimäki et al 10 report about a moderate midterm risk of revision of RSAs of 5% with infection being the most common reason for revision.…”
Section: Discussionmentioning
confidence: 99%
“…The first of these articles looked at a comparison of short term (six year) survival between stemmed and stemless shoulder arthroplasty with the second article comparing infection rates between reverse shoulder replacement (RSR) and hemiarthroplasty. 11,12 The population in Rasmussen et al's article in the Journal of Shoulder and Elbow surgery 12 was patients with osteoarthritis (OA) who underwent shoulder replacement between 2011 and 2016 in Denmark, Finland, Norway or Sweden. The intervention was stemless shoulder replacement and comparator was the more frequently implanted stemmed shoulder replacement.…”
Section: Shoulder and Elbowmentioning
confidence: 99%